Peran LSM ‘Konservasi Kima Toli-Toli – Labengki’ Untuk Kelestarian Kima Sebagai Pelindung Ekosistem Laut - Dian Trianita Lestari; Iriyani Astuti Arief; Shinta Arjunita Saputri (Department of Political Science - Universitas Sains Al-Qur’an, 2020)
This study aims to determine and describe the role of Toli-Toli-Labengki Giant Clam Conservation for the giant clams’ sustainability in Toli-Toli Village, Lalonggasumeeto District. This study uses a qualitative method by applying Green Thought and International Organizations theory to see the role of NGOs in the restoration of giant clam habitat areas. Meanwhile, the data collection techniques used was interviews, literature study and documentation with data analysis techniques consisting of three stages, namely data reduction, data presentation and drawing conclusions. The results showed that the NGO Toli-Toli – Labengki Giant Clam Conservation played a role as: an independent actor who acts as an international organization and is not merely implementing the interests of the organization or its members, but for the common good; because for negotiations and produce mutually beneficial decisions by educating residents about the importance of giant clam for the sustainability of the coastal ecosystem of Toli-Toli Village so that in the end the community also get benefit; and instruments for collaborating with NGO Naturevolution to reduce plastic waste on the coastal area of the village to Labengki island. Considering the benefits of giant clams to marine ecosystems and the giant clams cultivation requires quite a lot of funds, this NGO should get more attention and support from both local and national governments.